Diffuse Idiopathic Pulmonary Neuroendocrine Cell Hyperplasia (DIPNECH) Syndrome and Carcinoid Tumors With/Without NECH: A Clinicopathologic, Radiologic, and Immunomolecular Comparison Study. (May 2018) - Mengoli, Maria Cecilia; Rossi, Giulio; Cavazza, Alberto; Franco, Renato; Marino, Federica Zito; Migaldi, Mario; Gnetti, Letizia; Silini, Enrico Maria; Ampollini, Luca; Tiseo, Marcello; Lococo, Filippo; Fournel, Ludovic; et al.
Abstract : The diagnostic criteria of diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) are not well defined, and DIPNECH can be mistaken for carcinoids associated with neuroendocrine cell hyperplasia (NECH). In this study, we compared clinical, radiologic, histologic, immunohistochemical, and molecular features of DIPNECH and isolated carcinoids with/without NECH. The study population included 151 cases (77 female patients and 74 male patients), 19 with DIPNECH and 132 with carcinoids with/without NECH. None of the cases displayed molecular alterations or anaplastic lymphoma kinase expression. Compared with individuals with carcinoids with/without NECH, patients with DIPNECH were more likely to be female individuals ( P <0.0001), nonsmokers ( P =0.021), and symptomatic, and to have an obstructive/mixed respiratory defect, peripheral location of the lesions, and air trapping ( P <0.0001) on chest computed tomography, and constrictive bronchiolitis on histology ( P <0.0001). Among immunohistochemical markers, DIPNECH was associated with higher expression of thyroid transcription factor-1, CD10, and gastrin-releasing peptide/bombesin-like peptide ( P <0.0001). Yet, when a purely histopathologic definition of DIPNECH was applied, 40% of isolated carcinoids also met the diagnostic criteria for DIPNECH, even in the absence of symptoms and/or radiologic abnormalities. Therefore, as DIPNECH represents a distinct clinical syndrome, we suggest the term DIPNECH be limited to cases presenting with respiratory symptoms, functional and/or radiologic abnormalities, and constrictive bronchiolitis on histology.